Solar district heating with solar desalination using energy storage material for domestic hot water and drinking water – Environmental and economic analysis. (February 2022) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Mirjalily, Seyed Ali Agha; Muhammad, Taseer
Highlights: Solar still used for producing the hot water and drinking water. Domestic hot water production of solar still using NEPCM is improved by 41.9%. CuO nanoparticles added in PCM was reduced the melting temperature by 2.5 °C. Environmental, exergoeconomic and cost of water production analysis were studied. Abstract: Solar district heating application is one of the most widely used techniques, which has been considered due to its environmental friendliness, low cost and availability in most parts of the world. In this present study, a solar desalination system has been used to district heating and drinking water for domestic applications under climatic conditions of Tehran, Iran. Nano-enhanced phase change material is used in solar desalination water to store thermal energy and enhance the performance of district heating system. The anthracite porous surface bed was used to enhance the solar radiation. The copper oxide nanoparticles were mixed with paraffin wax at a concentration of 0.2 wt% as an energy storage media to enhance the thermal characteristic of phase change material and it was poured into the six copper pipes placed in the anthracite. They found that the hot water generation for district heating of domestic applications in solar desalination with nano-enhanced phase change material and porous surface absorber is 41.94% higher than conventional solar desalination. Also, The CO2 removal based on environmental and exergoenvironmental analysis in the solar stills using nano-enhanced phase change material, and porous surface absorber was increased by 41.7% and 18.4%, respectively.